2013
DOI: 10.1155/2013/208705
|View full text |Cite
|
Sign up to set email alerts
|

Essential Roles of PKA, iNOS, CD95/CD95L, and Terminal Caspases in Suppression of Eosinopoiesis by PGE2 and Other cAMP‐Elevating Agents

Abstract: Up- and downregulation of eosinopoiesis control pulmonary eosinophilia in human asthma. In mice, eosinopoiesis is suppressed in vitro by prostaglandin E2 (PGE2) and in vivo by diethylcarbamazine, through a proapoptotic mechanism sequentially requiring inducible NO synthase (iNOS) and the ligand for death receptor CD95 (CD95L). We examined the roles of iNOS, cAMP-mediated signaling, caspases, and CD95L/CD95 in suppression of eosinopoiesis by PGE2 and other agents signaling through cAMP. Bone-marrow collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Previous studies [24, 25] had shown DEC effects to be dependent on inducible NO synthase, which is an essential part of a proapoptotic pathway activated by a variety of soluble ligands [30]. The present study makes it unlikely that DEC induces or activates iNOS directly, as no effect of DEC was observed in 5-LO-deficient mice.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Previous studies [24, 25] had shown DEC effects to be dependent on inducible NO synthase, which is an essential part of a proapoptotic pathway activated by a variety of soluble ligands [30]. The present study makes it unlikely that DEC induces or activates iNOS directly, as no effect of DEC was observed in 5-LO-deficient mice.…”
Section: Discussionmentioning
confidence: 47%
“…Eosinopoiesis in liquid culture was strictly dependent on IL-5, and culture conditions were adequate for demonstrating both enhancing and suppressive effects [9, 29, 30]. Cells present in 7-day culture were resuspended, collected, counted, cytocentrifuged, and stained for eosinophil peroxidase (EPO; cyanide-resistant peroxidase), a murine eosinophil lineage-specific marker, present from the earliest precursors to terminally differentiated eosinophils [27, 28], and scored as detailed in [9].…”
Section: Methodsmentioning
confidence: 99%
“…Eosinopoiesis and its modulation by various agents were strictly dependent upon IL‐5 (Gaspar‐Elsas et al ., 1997; 2000a; 2009). Where indicated, cultures received α‐GalCer (10 −6 –10 −12 M), together with indomethacin (10 −7 M), aspirin (10 −7 M) (Xavier‐Elsas et al ., ; Queto et al ., ), the iNOS inhibitor aminoguanidine (10 −4 M; Queto et al ., ) or the caspase inhibitor zVAD‐fmk (20 μM; de Luca et al ., ). Each agonist or inhibitor was added only once, immediately after IL‐5, at the beginning of the culture period.…”
Section: Methodsmentioning
confidence: 97%
“…We had previously characterized (Jones et al ., ; Gaspar‐Elsas et al ., ; Queto et al ., ) a proapoptotic mechanism for regulation of eosinophil production, dependent upon iNOS and the ligand for CD95/Fas (CD95L/FasL), which operates in vivo during airway allergen challenge of sensitized mice, and accounts for the therapeutic effect of diethylcarbamazine (DEC), a leukotriene synthesis inhibitor (Matthews and Murphy, ), in experimental asthma (Queto et al ., ). Although activation of this mechanism by DEC and other drugs (de Luca et al ., ) prevents the induction of eosinophilia by allergen (Masid‐de‐Brito et al ., ), its blockade by LTD 4 and non‐steroidal anti‐inflammatory drugs (NSAIDs) (Xavier‐Elsas et al ., ) protects developing eosinophils from apoptosis. Furthermore, dexamethasone protects developing eosinophils from apoptosis by preventing expression of iNOS (de Luca et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation